URBAN DEVELOPMENT AND ADOLESCENT BEHAVIOUR IN SOCIAL PROBLEM: A CASE STUDY OF NORTH EAST PENANG, MALAYSIA - Abdul Latip, Normah (PLANNING MALAYSIA, 2020)
The purpose of the study is to explore a possible connection between urban development and the social problem faced by an adolescent, the group who considered to be a trivial problem and less been discussed detailed in previous studies. The establishment of theory and research procedure to mitigate this subject's exploration leads to the analysis of the relationship of determination factors between adolescent social problems and urban development, the exploration study approach used with the questionnaire that equips with nominal and ordinal scales as a tool. The random sampling method practically implemented to the target group, which is an adolescent from several residential in Penang, Malaysia. George Town, Bukit Jambul, Ayer Itam, Gelugor, Jelutong, Tanjung Tokong and Tanjung Pinang select as areas of study. The preliminary findings show a significant connection between urban development and adolescent behavior pattern. This study's results indicate that the event and the elements of municipal facilities and family ties include the role of parents as a strong influence on youth involvement in social problems. It can also be used as a reference for future research in urban development factors and enrich the study of welfare and social security of adolescents towards sustainable urban communities.